Noninvasive Assessment of Preload Reserve Enhances Risk Stratification of Patients With Heart Failure With Reduced Ejection Fraction. (May 2018) - Matsumoto, Kensuke; Onishi, Akira; Yamada, Hirotsugu; Kusunose, Kenya; Suto, Makiko; Hatani, Yutaka; Matsuzoe, Hiroki; Tatsumi, Kazuhiro; Tanaka, Hidekazu; Hirata, Ken-Ichi
Abstract : Background: The leg-positive pressure maneuver can safely and noninvasively apply preload stress without increase in total body fluid volume. The purpose of this study was to determine whether preload stress could be useful for risk stratification of patients with heart failure with reduced ejection fraction. Methods and Results: For this study, 120 consecutive patients with heart failure with reduced ejection fraction were prospectively recruited. The stroke work index was estimated as product of stroke volume index and mean blood pressure, and the E/e′ ratio was calculated to estimate ventricular filling pressure. The echocardiographic parameters were obtained both at rest and during leg-positive pressure stress. During the median follow-up period of 20 months, 30 patients developed adverse cardiovascular events. During preload stress, stroke work index increased significantly (from 3280±1371 to 3857±1581 mm Hg·mL/m 2 ; P <0.001) along with minimal changes in ventricular filling pressure (E/e′, from 16±10 to 17±9; P <0.05) in patients without cardiovascular events. However, patients with cardiovascular events showed impairment of Frank–Starling mechanism (stroke work index, from 2863±969 to 2903±1084 mm Hg·mL/m 2 ; P =0.70) and a serious increase in E/e′ ratio (from 19±11 to 25±14; P <0.001). Both the patients without contractile reserve and those without diastolic reserve exhibited worse event-free survival than the others ( P <0.001). In a Cox proportional-hazards analysis, the changes in stroke work index (hazard ratio: 0.44 per 500 mm Hg·mL/m 2 increase; P =0.001) and in E/e′ (hazard ratio: 2.58 per 5-U increase; P <0.001) were predictors of cardiovascular events. Conclusion: Contractile reserve and diastolic reserve during leg-positive pressure stress are important determinants of cardiovascular outcomes for patients with heart failure with reduced ejection fraction. Abstract : Supplemental Digital Content is available in the text.